ADJUSTMENT TO COLLEGE WORK AND ITS RELATIONSHIP WITH PSYCHOLOGICAL DISTRESS IN INTERNATIONAL STUDENTS AT THE UNIVERSITY OF INDONESIA - Marella, Bianca; Prasetyawati, Wuri (Faculty of Psychology, Diponegoro University, 2020)
Relocation can be a challenging and stressful experience for most international students. The demands of cultural adjustments frequently place international students at greater risk for various psychological problems than students in general. This research aims to describe the relationship between adjustment to college work problems and psychological distress. A cross-sectional survey with a self-completion questionnaire was conducted in a convenience sample of international students in Universitas Indonesia. Using convenience sampling, 107 international students (51.4% male, mean age = 25.7 years, SD = 5.65) completed the Hopkins Symptoms Checklist-25 (HSCL-25), a measurement of psychological distress, and the Mooney Problem Checklist â€“ Adjustment to College Work scale as a measurement of adjustment to college work. Using the HSCL-25 score 1.75 as a cut-off, 28 participants (26.2%) reports a high psychological distress level. Pearson correlation demonstrates that there is no significant correlation between adjustment to college work problems and psychological distress. Further analysis for each adjustment-problem item was carried out to explore specific academic problems faced by international students. We found that the problems â€œWorrying about examinationâ€ (r = .194, p < .05) and â€œFearing in failure in collegeâ€ (r = .218 p < .05) were significantly associated with psychological distress. It is advisable for education institutions that accept international students to provide academic counselors or train local students to help international students.